MODELING OF PENSION PAYMENT DYNAMICS: FACTORS, TRENDS, FORECASTS - Дворник, Інна; Стадник, Вікторія (Demography and social economy, 2026)
The article analyzes the dynamics of the average pension size in Ukraine during 2004—2025. The relevance of the study lies in the identification of the transformation of the country’s economic growth into an increase in the welfare of pensioners. The forecast of the average pension size for 2026 was performed using the methods of correlation modeling, moving average, and exponential smoothing. It was found that all methods demonstrate different dynamics of pension growth; the most optimal and realistic can be considered the forecast obtained using the exponential smoothing method, since it best takes into account the trends of recent years and possible changes in growth rates. The forecast using the regression polynomial model of degree 5 should be considered optimistic. Using correlation-regression analysis, the strength and direction of the relationship between the size of pensions and macroeconomic indicators: gross domestic product per capita, average wage. It was determined that there is a pronounced positive statistical relationship between them, which gives grounds to indicate the dependence of the size of pension payments on the economic capacity of the state. The results of modeling indicate that pension payments have shown a steady upward trend. However, an increase in the nominal size of pensions is not always accompanied by an equivalent increase in their real value, which confirms the impact of inflation. The mechanism of interaction between the pension size and macroeconomic indicators is highlighted: gross domestic product affects pension payments through employment, wage levels, receipts to the Pension Fund, and the state’s budgetary capabilities. At the same time, this relationship is not completely linear, but depends on the demographic structure, shadow economy, pension system, and inflationary processes. Economically sound solutions in the field of the pension system of Ukraine are proposed — indexation of pensions, strengthening the connection of pension payments with labor income, strengthening the financial base of the Pension Fund, taking into account inflation risks in pension forecasting, differentiation of the pension system, and integration with macroeconomic policy. REFERENCES / ЛІТЕРАТУРА 1. Pension Fund of Ukraine (2025). Information on the number of pensioners by types and amounts of assigned pensions as of April 1, 2025. https://www.pfu.gov.ua/2171384-informatsiya-shhodo-chyselnosti-pensioneriv-za-vydamy-ta-rozmiramy-pryznachenyhpensij-stanom-na-1-kvitnya-2025-roku/ [Пенсійний фонд України (2025). Інформація щодо чисельності пенсіонерів за видами та розмірами призначених пенсій станом на 1 квітня 2025 року]. 2. Libanova, E. M. (Ed.). (2006). National system of mandatory state social insurance: current problems and development strategy: monograph. Kyiv: Ptoukha Institute for Demography and Social Studies of the National Academy of Sciences of Ukraine. [Лібанова, Е. М. (Ред.). (2006). Національна система загальнообов’язкового державного соціального страхування: сучасні проблеми та стратегія розвитку: монографія. Київ: Інститут демографії та соціальних досліджень НАН України]. 3. Voinalovych, I. (2024). Current state and vectors of development of pension provision in Ukraine. Economy and society, 64. https://doi.org/10.32782/2524-0072/2024-64-95 [Войналович, І. (2024) Сучасний стан і вектори розвитку пенсійного забезпечення в Україні. Економіка та суспільство, 64]. 4. Boyar, D., & Aleksandrova, M. (2021). Analysis of the dynamics of pension provision in Ukraine. https://conf.ztu.edu.ua/wp-content/uploads/2021/01/230.pdf [Бояр, Д., Александрова, М. (2021). Аналіз динаміки пенсійного забезпечення в Україні]. 5. Cherenko, L. et al. (2024) The quality of life of the population of Ukraine and the first consequences of the war: a monograph. Kyiv: NAS of Ukraine, Institute for Demography and Quality of Life Studies. [Черенько, Л.та ін. (2024). Якість життя населення України та перші наслідки війни: монографія. Київ: Національна академія наук України, Інститут демографії та проблем якості життя НАН України]. 6. Pikus, R., & Treitiak, O. (2024) Prospects for the development of non-state pension provision in Ukraine. Economy and society, 57. https://doi.org/10.32782/2524-0072/2024-59-17 [Пікус, Р., & Трейтяк, О. (2024). Перспективи розвитку недержавного пенсійного забезпечення в Україні. Економіка та суспільство, 57]. 7. Kondrat, I. (2025) Issues and future directions of accumulative pension provision in Ukraine. Economy and society, 76. https://doi.org/10.32782/2524-0072/2025-76-37 [Кондрат, І. (2025) Проблеми та перспективи розвитку накопичувального пенсійного забезпечення в Україні. Економіка та суспільство, 57]. 8. Rybalchenko, L., & Guseva, K. (2017). Formalization of the ukrainian middle pension by using econometric methods. Economics and society, 12, 772—775. https://economyandsociety.in.ua/journals/12_ukr/129.pdf [Рибальченко, Л., & Гусєва, К. (2017). Прогнозування середньої пенсії українця із застосуванням економетричних методів. Економіка і суспільство, 12, 772—775.]. 9. Lavruk, N., & Grendei, N. (2017) Current status and forecasting of revenues to the Pension Fund of Ukraine. Economics and society, 13, 1006—1011. https://economyandsociety.in.ua/journals/13_ukr/168.pdf [Лаврук, Н., & Грендей, Н. (2017). Сучасний стан та прогнозування надходжень до Пенсійного фонду України. Економіка і суспільство, 13, 1006—1011]. 10. Gutsalova, Yu. (2013) Model for forecasting the income of the Pension Fund budget (based on materials from the Dnipropetrovsk region). Economic Bulletin. Finance, 2, 140—146. https://ev.nmu.org.ua/docs/2013/2/EV20132_140-146.pdf [Гуцалова, Ю. (2013) Модель прогнозування надходження доходів бюджету Пенсійного фонду (на матеріалах Дніпропетровської області). Економічний вісник. Фінанси, 2, 140—146]. 11. Bredyuk, V., & Joshi, O. (2013). Economic and mathematical modeling of pension dynamics in Ukraine. Scientific notes. Series “Economy”, 22, 133—136. https://eprints.oa.edu.ua/id/eprint/2146/1/28.pdf [Бредюк, В., & Джоші, О. (2013) Економіко-математичне моделювання динаміки пенсійного забезпечення в Україні. Наукові записки. Серія «Економіка», 22, 133—136]. 12. Telichko, N. (2013) Actuarial methods to ensure of the pension system’s financial sustainability. Bulletin of the Volodymyr Dahl East Ukrainian National University, 3 (192), Part II, 164—171. Lugansk: Publishing House of the Volodymyr Dahl East Ukrainian National University. https://dspace.luguniv.edu.ua/xmlui/bitstream/handle/123456789/719/Telich.pdf?sequence=1&isAllowed=y [Телічко, Н. (2013) Актуарні методи забезпечення фінансової стійкості пенсійної системи. Вісник Східноукраїнського національного університету імені Володимира Даля, 3 (192), II ч., 164—171. Луганськ: Видавництво СНУ ім. В. Даля]. 13. Dvornyk, I. (2013). Theoretical and methodological principles of the formation of the income level of the rural population. Scientific Bulletin of the National University of Life and Environmental Sciences of Ukraine. Economics, Agricultural Management, Business, 181 (4), 114—122. http://nbuv.gov.ua/UJRN/nvnau_econ_2013_181(4)__19. [Дворник, І. (2013). Теоретико-методологічні засади формування рівня доходів сільського населення. Науковий вісник Національного університету біоресурсів і природокористування України. Сер.: Економіка, аграрний менеджмент, бізнес, 181 (4), 114—122]. 14. Dvornyk, I. (2017). The estimation of influence of basic factors on the formation of rural population’s income. Demography and social economy, 2 (30), 211—224. https://doi.org/10.15407/dse2017.02.211 [Дворник, І. (2017). Оцінка впливу основних факторів на формування доходів сільського населення. Демографія та соціальна економіка, 2 (30), 211—224]. 15. World Bank Group (2025). Ukraine’s GDP per capita. https://www.worldbank.org/ext/en/home [Група Світового банку (2025). ВВП України на душу населення]. 16. Public organization Ukrainian Center for Economic and Political Research named after Oleksandr Razumkov (2023). The level of pension provision for pensioners and persons with disabilities in Ukraine compared to the countries of the European Union. https://razumkov.org.ua/images/2023/04/21/analitych_materialy.pdf [Громадська організація Український центр економічних і політичних досліджень імені Олександра Разумкова (2023). Рівень пенсійного забезпечення пенсіонерів та осіб з інвалідністю в Україні у порівнянні з країнами Європейського Союзу].